Multiple Rapid Swallow Responses During Esophageal High-Resolution Manometry Reflect Esophageal Body Peristaltic Reserve - Shaker, Anisa (2013)
OBJECTIVES: Dysphagia may develop following antireflux surgery as a consequence of poor esophageal peristaltic reserve. We hypothesized that suboptimal contraction response following multiple rapid swallows (MRS) could be associated with chronic transit symptoms following antireflux surgery. METHODS: Wet swallow and MRS responses on esophageal high-resolution manometry (HRM) were characterized collectively in the esophageal body (distal contractile integral (DCI)), and individually in each smooth muscle contraction segment (S2 and S3 amplitudes) in 63 patients undergoing antireflux surgery and in 18 healthy controls. Dysphagia was assessed using symptom questionnaires. The MRS/wet swallow ratios were calculated for S2 and S3 peak amplitudes and DCI. MRS responses were compared in patients with and without late postoperative dysphagia following antireflux surgery. RESULTS: Augmentation of smooth muscle contraction (MRS/wet swallow ratios > 1.0) as measured collectively by DCI was seen in only 11.1% with late postoperative dysphagia, compared with 63.6% in those with no dysphagia and 78.1% in controls (P≤0.02 for each comparison). Similar results were seen with S3 but not S2 peak amplitude ratios. Receiver operating characteristics identified a DCI MRS/wet swallow ratio threshold of 0.85 in segregating patients with late postoperative dysphagia from those with no postoperative dysphagia with a sensitivity of 0.67 and specificity of 0.64. CONCLUSIONS: Lack of augmentation of smooth muscle contraction following MRS is associated with late postoperative dysphagia following antireflux surgery, suggesting that MRS responses could assess esophageal smooth muscle peristaltic reserve. Further research is warranted to determine if antireflux surgery needs to be tailored to the MRS response.